Evaluation of medim chain fatty acids as a dietary additive in nursery diets - Thompson, Katelyn A.; Gebhardt, Jordan T.; Clark, Anne B.; Woodworth, Jason C.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Dritz, Steven S. (My University, 2017)
A total of 360 pigs [(400 × 200, DNA, Columbus, NE initially 6.7 kg BW) were used in a 35-d study to evaluate the effects of medium chain fatty acids (MCFA; C6, C8, and C10) as a dietary additive on nursery pig growth performance. Pigs were weaned at 21 d of age and allotted to pens based on BW. Pigs were fed a commercial starter diet for 6-d prior to the start of the experiment. Pens of pigs were then assigned to 1 of 8 dietary treatments in a randomized block design by BW with 5 pigs per pen and 9 pens per treatment. Dietary treatments were: 1) a control diet without MCFA; 2-5) control diet containing a 1:1:1 blend of C6, C8, and C10 at 0.25, 0.50, 1.0 or 1.50% total MCFA; 6-8) control diet containing 0.50% C6, C8 or C10. Dietary treatments were fed for 35 d with pig weights and feed disappearance measured weekly to determine ADG, ADFI, and G:F. Data were analyzed using a generalized linear mixed model with pen as the experimental unit. For the overall period (d 0 to 35), pigs fed increasing MCFA blend had improved (linear, P< 0.05) final BW, ADG, ADFI, and G:F. Pigs fed C6 alone or C8 alone had increased (P<0.05) ADG, G:F, and final BW compared to pigs fed the control diet. There was no evidence (P>0.05) for difference between feeding the MCFA alone at 0.50% of the diet compared to pigs fed the 0.5% 1:1:1 blend diet. In conclusion, increasing MCFA blend improved growth performance. Additionally, inclusion of C6 or C8 to the diet resulted in improved ADG and G:F compared to pigs fed the control diet.
Keywords: Fall 2017